1996
DOI: 10.2307/2061763
|View full text |Cite
|
Sign up to set email alerts
|

The impact of state-level restrictions on abortion

Abstract: This research examines 23 different laws passed by state governments in an effort to restrict the number of abortions. It assesses both laws passed and laws actually enforced after the Supreme Court permitted states to restrict access to abortion in 1989. None of the policy actions by state governments has had a significant impact on the incidence of abortion from 1982 to 1992. Abortion rates continue to reflect past abortion rates, the number of abortion providers, whether the state funds abortions for Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Numerous articles during the 1990s mentioned the Webster and Cusey decisions, the expectation that they will lead states to pass more restrictions, and the thought that it would take time before the situation could be assessed more fully (Hansen 1993;Goggin 1993;Halva-Neubauer 1993;Meier et al 1996). Some speculated that with an increase in restrictions, an impact on abortion rates may emerge (Hansen 1993;Meier et al 1996). This study seeks to revisit that question now that sufficient time has passed for an assessment to be made.…”
Section: Wadementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous articles during the 1990s mentioned the Webster and Cusey decisions, the expectation that they will lead states to pass more restrictions, and the thought that it would take time before the situation could be assessed more fully (Hansen 1993;Goggin 1993;Halva-Neubauer 1993;Meier et al 1996). Some speculated that with an increase in restrictions, an impact on abortion rates may emerge (Hansen 1993;Meier et al 1996). This study seeks to revisit that question now that sufficient time has passed for an assessment to be made.…”
Section: Wadementioning
confidence: 99%
“…Some of the most widely adopted policies have been informed consent requirements mandating abortion-specific state-determined information and counseling; parental involvement requirements; and waiting periods prior to obtaining an abortion, usually 24 hours. During the 1990s, national abortion rates dropped (Henshaw 1998 Abortion Restrictions 473 (Hansen 1993;Wetstein 1995;Meier et al 1996;Mete 2000). This study explores the relationship between abortion regulations and abortion rates at the state level for the years 1988-96.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Meier et al (1996) studied the impact of 23 di erent state laws that purport to restrict the number of abortions. Their ®ndings suggested that none of the restrictions had a signi®cant impact on the rates of induced abortion from 1982 to 1992.…”
Section: I I R E V I E W O F T H E L I T E R a T U R Ementioning
confidence: 99%
“…Often, government attempts to regulate fertility either have failed or resulted in unintended consequences. For example, failure of conservative governments to support contraception has resulted in increased abortion rates, while restrictive laws in the U.S. have apparently not altered abortionseeking behavior (Meier et al, 1996).…”
mentioning
confidence: 99%